Stability and Delay of Network-Diversity Multiple Access with Backlog Retransmission Control - Robles, Ramano (2017)
The Second International Conference on Advances in Signal, Image and Video Processing - from Sensing to Applications (SIGNAL 2017). 21 to 25, May, 2017, 5Gsignalwave. Barcelona, Spain.